Fizjoterapia w hipertonii przepony – opis przypadku = Physiotherapy in hypertonia of the diaphragm - a case study - Kochański, Bartosz; Kałużny, Krystian; Kałużna, Anna; Wołowiec, Łukasz; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kochański Bartosz, Kałużny Krystian, Kałużna Anna, Wołowiec Łukasz, Zukow Walery. Fizjoterapia w hipertonii przepony – opis przypadku = Physiotherapy in hypertonia of the diaphragm - a case study. Journal of Education, Health and Sport. 2016;6(7):471-478. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58628 http://ojs.ukw.edu.pl/index.php/johs/article/view/3710 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 25.07.2016. Fizjoterapia w hipertonii przepony – opis przypadku Physiotherapy in hypertonia of the diaphragm - a case study Bartosz Kochański1, Krystian Kałużny1, Anna Kałużna1, Łukasz Wołowiec2, Walery Zukow3 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2 II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 3 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy; Streszczenie. Przepona to główny miesień oddechowy człowieka, który oddziela od siebie przestrzenie o zupełnie innych warunkach fizycznych oraz funkcjach. Jednym z typów dysfunkcji przepony jest hipertonia przepony, która charakteryzuje się jej zbyt niskim ułożeniem podczas wydechu. W takiej sytuacji przepona nie ulega odpowiedniemu wznoszeniu podczas fazy wydechu co przekłada się na spłaszczenie jej kopuł. U pacjentów obserwuje się tor oddychania określany, jako wybitnie brzuszny ze zwiększonym ciśnieniem podprzeponowym. W pracy przedstawiono pacjenta o typowym obrazie klinicznym hipertonii przepony. Na podstawie analizy piśmiennictwa oraz doświadczeń własnych zaprezentowano wybrane techniki fizjoterapeutyczne stosowane w hipertonii przepony. Abstract The diaphragm is the main breathing muscle that separates the spaces with completely different physical conditions and functions. One type of the diaphragm dysfunction is hypertonia diaphragm, which is characterized by the arrangement is too low during exhalation. In this case, the diaphragm is not appropriate during the ascent phase of the exhaust which results in flattening of the domes. Patients observed of breathing referred to as eminently fever with increased pressure under the diaphragm. The paper presents a patient with a typical clinical picture of hypertonia diaphragm. Based on the analysis of the literature and our own experience presents selected physiotherapy techniques used in hypertonia diaphragm. Słowa kluczowe: hipertonia przepony, przepona, fizjoterapia. Key words: hipertonia diaphragm, diaphragm, physiotherapy.